Attachment to God and positive orientation: A systematic review - Facchino, Antonio Pio ca. 20./21. Jh. (Archive for the psychology of religion, 2026)
Attachment to God (ATG) refers to the perceived emotional bond between the believer and God, who serves as an attachment figure. Positive orientation is the propensity to think positively about various domains related to the self, life, and the future and has three dimensions, namely self-esteem, life satisfaction, and optimism. A systematic review was carried out on Scopus, Web of Science, and PsycInfo databases (until November 2022) to summarize evidence on the associations between ATG and positive orientation following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The risk of bias was assessed using the Newcastle-Ottawa scale. The search produced 81 records, and 14 met the eligibility criteria, including 16 studies. Cross-sectional studies showed a low risk of bias, and longitudinal/cohort studies high risk. The included studies provided evidence of significant associations between the ATG construct or its subtypes and at least an indicator of positive orientation. Overall, secure ATG was positively associated with one or more dimensions of positive orientation, whereas anxious and avoidant ATG showed negative associations. No study has examined positive orientation as a whole. Some inconsistencies emerged in the results due to the heterogeneity of the tools used to assess both ATG and positive orientation indicators, the presence of uncontrolled variables, and the predominance of Christian participants. Overall, these findings offer an initial contribution to understanding the relationship between ATG and positive orientation, also highlighting the need for future research to strengthen these results. Specifically, further studies should assess positive orientation as a unified construct using instruments specifically designed for this purpose.